Electron beam irradiation-induced structural changes increase the antioxidant activities of egg white protein. (August 2019) - Liu, Xuanting; Liu, Jingbo; Zhang, Wenqi; Han, Shuo; Zhang, Ting; Liu, Boqun
Abstract: Electron beam irradiation (EBI) is a widely applied non-thermal technology for food processing. To investigate the influence of EBI on the antioxidant activities and the structure of proteins, we treated egg white protein (EWP) with EBI and tracked the changes in antioxidant activities as well as in the structure of EWP. The ABTS + free radical scavenging rate significantly increased from 30.16 ± 1.45% to 49.48 ± 1.53% ( P  <  0.05 ) after the EBI treatment. The α-helix content decreased from 26.7% to 17.4%, while the β-parallel content increased from 35.1% to 56.6%. Additionally, the particle size of EWP increased, while the absolute Zeta potential decreased. The surface hydrophobicity and the free –SH and total –SH contents increased simultaneously. These results indicate that the buried hydrophobic amino acids and the –SH group become exposed to the environment after EBI treatment. This study can provide a basis for further exploration of the mechanism of EBI applications to improve antioxidant capability. Highlights: EBI enhances the ABTS + capacity of EWP 1.5 times more than the untreated group. EBI treatment breaks the S–S bond and exposes the hydrophobic amino acid residues. EBI treatment increases the antioxidant activity of EWP and leads to oligomerization. EBI treatment changes the microstructure of EWP into "honeycomb" microstructures.